The Influence of Workload and Role Ambiguity on Work Stress among Employees of the Department of Trade and Industry of Gowa Regency - Juhernawati Juhernawati; Muh. Nur; Andi Risfan Rizaldi (Journal Social Society, 2026)
Work stress is an important issue in Indonesian public-sector organizations because local government agencies are required to deliver effective public services while operating within bureaucratic procedures, hierarchical structures, and accountability demands. In this context, excessive workload and unclear job responsibilities may reduce employee performance, productivity, and organizational effectiveness. This study aims to analyze the effect of workload and role ambiguity on work stress among employees of the Department of Trade and Industry of Gowa Regency. This research employed a quantitative explanatory design. Data were collected using a structured questionnaire measured with a five-point Likert scale, covering indicators of workload, role ambiguity, and work stress. The population consisted of 45 employees, and a saturated sampling technique was applied, whereby all members of the population were selected as respondents. The data were analyzed using multiple linear regression with SPSS version 29. The findings show that workload has a positive and significant effect on work stress (? = 0.221; t = 4.095; p < .001). Role ambiguity also has a positive and significant effect on work stress and shows a stronger influence than workload (? = 0.491; t = 9.844; p < .001). Simultaneously, workload and role ambiguity significantly explain work stress, with an F-value of 111.372, p < .001, and R² = 0.841. These results indicate that employee work stress is shaped not only by the amount of work assigned, but also by uncertainty regarding duties, authority, and responsibilities. Practically, the organization should conduct periodic workload assessments, ensure fair task distribution, develop clear job descriptions, improve communication of responsibilities and authority, and establish employee support programs such as supervision, counseling, or stress management training to reduce work stress and improve organizational performance.